A comprehensive meta‐analysis of ZNF804A SNPs in the risk of schizophrenia among Asian populations. Issue 3 (11th February 2016) - Huang, Liang; Ohi, Kazutaka; Chang, Hong; Yu, Hao; Wu, Lichuan; Yue, Weihua; Zhang, Dai; Gao, Lei; Li, Ming
Abstract : Common variants in ZNF804A increased the risk of schizophrenia (and bipolar disorder), with low effect sizes in Europeans, which is in line with the polygenic nature of the illnesses, and implies that genetic analyses in small samples may not be sufficient to detect stable results. This notion is supported by the inconsistent replications of ZNF804A variations among individual small Asian samples, indicating the absence of definitive conclusions in this population. We collected psychiatric phenotypic and genetic data from Asian genome‐wide association (GWA) and individual replication studies, which include up to 13, 452 cases, 17, 826 healthy controls, and 680 families, that is, the largest‐scale study on ZNF804A in Asian populations to date. The European GWAS risk single nucleotide polymorphism (SNP) rs1344706 was nominally associated with schizophrenia in these Asian samples (one‐tailed P  = 4.26 × 10 −2, odds ratio [OR] = 1.048), and the association was further strengthened when bipolar disorder data was also included (one‐tailed P  = 1.85 × 10 −2, OR = 1.057). Besides, a non‐synonymous SNP rs1366842 in the exon 4 of ZNF804A was also associated with schizophrenia ( P  = 9.96 × 10 −3, OR = 1.095). We additionally analyzed other 163 SNPs covering ZNF804A region, but none of them showed any evidence of association. Though the two SNPs did not remain significant if we applied multiple corrections, our analysis should be interpreted as a primary replication study with in prior hypothesis, and rs1344706 and rs1366842 might confer a small but detectable risk of schizophrenia (and bipolar disorder) in Asians. Moreover, the current data suggest the necessity of replication analyses in a large enough scale samples. © 2016 Wiley Periodicals, Inc.